El Caribe en los libros de México. Autores y Temas (Tzintzun, Revista de Estudios Históricos, 2016)
The Caribbean has been a subject of study for many researchers in recent years, resulting in historical, sociological, political and cultural studies produced by specialists from high-level research and teaching institutions, agencies of the state and political and party-based organizations. More than an inventory of the contents of such studies, the author looks to identify those points of interest and analysis that are most representative of the studies of the region, from the prehispanic era to the present. In the text, the Cuban revolution stands out as one historical event that has generated special interest among Mexican researchers and politicians. In her journey, the author points out what has been written and how, and identifies the individuals who exercise the vocation of the historian. lt is also interesting to review the list of journals that have opened their pages to studies of the Caribbean. Especially important in the analysis are the relevant aspects of the theories and methods applied in the region and the sheer complexity of the area.